2022
DOI: 10.3233/jpd-223461
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Connection Between the Gut Microbiome and Parkinson’s Disease Symptom Progression and Pathology: Implications for Supplementary Treatment Options

Abstract: The contribution of the microbiota to induce gastrointestinal inflammation is hypothesized to be a key component of alpha-synuclein (aSyn) aggregation within the gastrointestinal (GI) tract in the pathological progression of Parkinson’s disease (PD). The function of the GI tract is governed by a system of neurons that form part of the enteric nervous system (ENS). The ENS hosts  100–500 million nerve cells within two thin layers lining the GI tract. The gut-brain axis (GBA) is the major communication pathway b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 121 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…These metabolic stability studies indicated that similar metabolites were observed in mouse, rat and human microsomes, suggesting that mice and rats are appropriate models for future animal studies of 18 F-C8-6-I. Emerging evidence supports the key role of the gut-brain connection in the pathogenesis of PD [65][66][67]. Our pharmacokinetics studies demonstrated a relatively high level of intestinal localization of 18 F-C8-6-I dimer probes which further suggests the potential applicability of our probe in gut-brain studies.…”
Section: Discussionmentioning
confidence: 62%
“…These metabolic stability studies indicated that similar metabolites were observed in mouse, rat and human microsomes, suggesting that mice and rats are appropriate models for future animal studies of 18 F-C8-6-I. Emerging evidence supports the key role of the gut-brain connection in the pathogenesis of PD [65][66][67]. Our pharmacokinetics studies demonstrated a relatively high level of intestinal localization of 18 F-C8-6-I dimer probes which further suggests the potential applicability of our probe in gut-brain studies.…”
Section: Discussionmentioning
confidence: 62%
“…The accumulation of SOD1 G93A in the spinal cord and neurons serves as a molecular marker of the progression of ALS in SOD1 G93A mice, beginning at 2 months of age; the aggregation of human SOD1 G93A protein is observed in the white and gray matter of the lumbar spine, accompanied by increased levels of glial fibrillary acidic protein (GFAP) and neuromuscular symptoms such as decreased muscle strength, which are indicative of neuromuscular degeneration. Additionally, disruption of GFAP in the ENS suggests that the gut microbiota affects gut neuromuscular structure as well as function, and that imbalance in the gut microbiota may act as a potential trigger for degenerative diseases ( 81 ). Further research is needed to fully understand this relationship.…”
Section: Dysbiosis Of the Gut Microbiota In Als Affects The Gbamentioning
confidence: 99%